HUBUNGAN PRAKTIK KERJA USAHA DAN EFIKASI DIRI DENGAN KESIAPAN KERJA MAHASISWA - Asmini, A; Karmeli, Elly; Asmawati, A (Fakultas Ekonomi dan Manajemen, 2025)
This study aims to determine the influence of business work practices and self-efficacy on students' work readiness. The type this study was associative study with a quantitative approach. The type of data used in this study was quantitative obtained directly from primary sources using a research instrument in the form of a questionnaire. The respondents in this study were 61 active students at the Faculty of Economics and Management, Samawa University. The selection of respondents was determined using probability sampling techniques with a simple random sampling method. The data analysis tool used was multiple linear regression, partial hypothesis test (t test), simultaneous hypothesis test (F test), and coefficient of determination test (R2). The results of this study showed that business work practices and self-efficacy had positive and significant effect on the work readiness of students at the Faculty of Economics and Management, Samawa University, either partially or simultaneously. The effect of business work practices and self-efficacy on the work readiness of students at the Faculty of Economics and Management, Samawa University was 74.3%, while the remaining of 25.7% was effected by other variables not examined in this study, such as career planning, adversity quotient, psychological capital, soft skills, motivation to enter the world of work, managerial skills, and social support.